A P-NTRU and secret key sharing techniques of access control scheme for big data storage in cloud - V. Divya, S; Monika, Bala; ., Venkadesh (International Journal of Engineering and Technology, 2018)
Outsourcing the ciphertexts in the cloud storage server becomes an effective way for storing the big data. However, verifying the access policy of the user and updating it regularly in the cloud server makes it really challenging. Various approaches have been proposed but they do not offer a complete solution. Hence, an efficient and secure proposed NTRU (P-NTRU) is proposed. Moreover, the P-NTRU system efficiently updates the stored cipher-text in the server when the ownerâ€™s access policy is changed. The proposed P-NTRU system enables the owner to verify the legitimacy of the user. With the introduction of the certificate authority, the burden of the data owner is highly reduced. Analysis proves that the proposed P-NTRU system is efficient and secure. Â Â